Acute hemorrhagic rectal ulcer: Experience in 11 patients at an urban acute care center in the USA. Issue 18 (May 2020) - Sugawa, Choichi; Culver, Ashley; Diebel, Mark; McLeod, Jennifer S.; Lucas, Charles E.
Abstract: Introduction: Acute hemorrhagic rectal ulcer (AHRU) is a rare entity which has most frequently been described in Japan and Taiwan literature. This study characterizes 11 AHRUs identified and managed at an urban acute care hospital in the United States of America (USA). Methods: A total of 2253 inpatients underwent colonoscopy. In 1172 patients (52%), colonoscopy was performed for evaluation of lower gastrointestinal (LGI) bleeding. Eleven (0.9%) of the 1172 patients with LGI bleeding had AHRU. Results: AHRU is characterized by a sudden onset of painless and massive lower rectal bleeding in elderly, bedridden patients (pts) with major underlying diseases. The endoscopic findings were classified into 4 types. All 11 ulcers were located in the distal rectum within 10 cm of the dentate line. All 11 patients required blood transfusion (mean = 3.7 units; range 2–9 units). Seven patients responded to blood, plasma, and platelet transfusions. The other 4 patients required endoscopic hemostasis. Three patients died within a month of colonoscopy from comorbidities. None had bleeding as a cause of death. Eight surviving patients did not have recurrent bleeding. Conclusion: AHRU does exist in the USA and should be considered as an important cause of acute lower GI bleeding in elderly, critically ill, and bedridden patients. AHRU should be recognized and managed correctly.